2022
DOI: 10.1016/j.jad.2021.09.087
|View full text |Cite
|
Sign up to set email alerts
|

The role of equanimity in mediating the relationship between psychological distress and social isolation during COVID-19

Abstract: Background Social isolation and the impact on mental health is a major concern during COVID-19. Trait equanimity is expected to protect individuals from psychological distress associated with social isolation. The aim of this study is to examine the link between social isolation and psychological distress via the mediator equanimity. It was hypothesised that objective (few social contacts) and perceived social isolation (loneliness) would predict psychological distress and that equanimity would me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
(60 reference statements)
0
11
0
1
Order By: Relevance
“…But there are still some aspects of the literature we included that demand our attention. The majority of the scales used to measure mindfulness in the included literature are the Mindful Attention Awareness Scale (MAAS), whereas Mann and Walker (2022) employed the 20-item Phenomenological Experience of Meditative Equanimity Scale. They did not employ the definition used by the majority of studies, as was indicated in the introduction of their literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But there are still some aspects of the literature we included that demand our attention. The majority of the scales used to measure mindfulness in the included literature are the Mindful Attention Awareness Scale (MAAS), whereas Mann and Walker (2022) employed the 20-item Phenomenological Experience of Meditative Equanimity Scale. They did not employ the definition used by the majority of studies, as was indicated in the introduction of their literature.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the study, mindfulness involves equanimity. It is described as being receptive to and accepting of all events ( Desbordes et al, 2014 ; Mann and Walker, 2022 ). Instead, equanimity is thought to be a component of mindfulness, as per historical meditation teachings theories ( Zeng et al, 2015 ; Mann and Walker, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This point is particularly salient in the context of COVID-19. Existential isolation may be catalysed by dramatic changes caused by pandemic conditions (e.g., routine, employment, family dynamics) and develop disproportionally in times of adversity ( Pinel et al, 2017 ), potentially explaining elevated rates of psychological distress ( Dozois, 2021 ; Mann and Walker, 2021 ; Ogrodniczuk et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…El presente trabajo aprovecha las ventajas expuestas de las CNN en reconocimiento de patrones y señales de audio para exponer una aplicación de control robótico asistencial en entornos residenciales, donde los comandos de navegación del robot, para ir a alguna locación especifica dentro de la residencia, son recibidos mediante voz y preprocesados empleando Coeficientes Cepstrales en las Frecuencias de Mel, para ser reconocidos por una red convolucional. Dada las necesidades de aislamiento experimentadas en la pandemia por covid [18], los robots asistenciales entran a jugar un papel fundamental en asistir en sus casas a personas que lo requieran.…”
Section: Introductionunclassified